Penguatan Sistem Hukum Nasional melalui Harmonisasi dan Penyelesaian Disharmoni Kewenangan Lembaga Negara - Muh Farhan Arfandy; Armi Putri Maharani; Muhamad Naka Kaiser; Auliah Ambarwati; Tegar Bimantoro (Jurnal Litigasi Amsir, 2026)
This study examines the problem of overlapping authority among high state institutions in Indonesia following the amendment to the 1945 Constitution of the Republic of Indonesia. The shift in the system towards the separation of powers and the proliferation of independent institutions has actually triggered disharmony, sectoral ego, and regulatory obesity, which has led to declining legal certainty and hampered the effectiveness of government. This study uses normative legal research methods with legislative, conceptual, and comparative approaches. This study examines the root of the problem and compares it with the constitutional practices of the United States and South Korea. The results of the study confirm that the availability of a dispute resolution forum in the Constitutional Court is not enough to unravel the conflict of authority in the field. Two main pillars are needed as fundamental solutions. First, the application of regulatory precision in the formation of rigid and firm laws to close the gap in gray areas, adopting the discipline of South Korean legislation. Second, the need to internalize a culture of constitutional compliance among the elite of state administrators, as is the tradition of the United States Constitution. This structural and cultural double improvement is an absolute prerequisite for realizing institutional harmonization, ensuring the upholding of legal certainty, and maintaining governance stability.